Subthalamic deep brain stimulation effects on odor identification in Parkinson's disease. (6th March 2014) - Fabbri, M.; Guedes, L. C.; Coelho, M.; Simão, D.; Abreu, D.; Rosa, M. M.; Silveira‐Moriyama, L.; Ferreira, J. J.
<x xml:space="preserve">Abstract</x> Background and purpose Olfactory dysfunction is common in Parkinson's disease (PD) and it is one of the earliest non‐motor symptoms. A few studies have suggested that deep brain stimulation of the subthalamic nucleus (STN‐DBS) could improve olfactory function. Our aim was to evaluate the acute effect of bilateral STN‐DBS on a commonly used smell test in PD patients. Methods Fifteen PD patients who underwent bilateral STN‐DBS and 15 controls were recruited. Patients and controls were tested for odor identification. Results No statistical differences were documented between ON and OFF STN‐DBS acute stimulation concerning olfaction. Controls presented a better performance for olfactory identification than patients. Conclusions Our exploratory study did not support that bilateral STN‐DBS could have an acute effect on olfactory function in PD patients.